EFEKTIVITAS PERAWATAN DIABETIC FOOT ULCER DENGAN MENGGUNAKAN MODERN DRESSING : HYDROFIBER DI PRAKTIK MANDIRI GRIYA AFIAT KOTA MAKASSAR - Wulansari; Wa Ode Sri Asnaniar; Nur Wahyuni Munir; Nur Ilah Phadila (CV. Adiba Aisha Amira, 2026)
Background: Diabetic Foot Ulcer (DFU) is a chronic complication of diabetes mellitus that can lead to disability or even amputation. The use of modern dressings such as Hydrofiber plays an essential role in accelerating wound healing, controlling exudate, preventing infection, and improving patient comfort. Objective: To evaluate the effectiveness of Hydrofiber dressing in DFU wound care, specifically in controlling exudate, maintaining wound moisture, preventing infection, reducing pain, and accelerating granulation and epithelialization in a DFU patient treated at Griya Afiat Wound Care Clinic, Makassar. Method : A case study was conducted on Mrs. R, a 51-year-old female with DFU on the dorsal side of the left foot extending to the calf. Wound assessment was performed using the Bates-Jensen Wound Assessment Tool. The intervention included wound cleansing, application of epithelial ointment, hydrophobic dressing, hydrofiber silver, and alginate dressing, followed by sterile gauze as a secondary dressing and an elastic bandage as tertiary dressing. Results: After two days of treatment, the wound size decreased from 104 cm² to 100 cm². Granulation tissue increased to approximately 60%, epithelialization reached 50%, necrotic tissue decreased by 25%, exudate was well-controlled, and no signs of infection were observed. The patient also reported a reduction in pain intensity during the treatment period. Conclusion: Wound care using Hydrofiber dressing proved effective in promoting DFU healing by controlling exudate, enhancing granulation and epithelialization, and preventing infection. Recommendation: Hydrofiber can be recommended as a primary option for chronic wound care, especially DFU. Further studies with larger sample sizes and longer treatment periods are needed to strengthen evidence of its effectiveness. Hydrofiber dressing is recommended as a primary option for managing chronic wounds such as DFU. Further research with larger sample sizes and longer observation periods is needed to strengthen evidence of its effectiveness